Do papel ao movimento, o cartaz animado em contexto de design de comunicação - Lourenço, Marisa Cristina Marques (2019)
The animated poster, studied from the technological evolution in the context of communication design, is the object of an investigation that describes the main changes (from the mechanized to the digital era), which tries to set the context and understand the emergence of the animated poster. The main references are the bibliographic and iconographic sources, and a survey to some animated poster designers, aiming to explain the evolution of animated posters – from paper to movement. The emphasis is on the relevance of technology along this process: from the early stage of the traditional poster until the digital era (from the description of the main printing methods); the poster in a digital context and the possibilities offered by the digital technology to the animated poster (including sound, movement and interactivity); and a scenario of changes that the animated poster will suffer with the technological development (addressing the remediation of new media and the prediction of a post-screen era, centered on the user’s body). By proposing a wide look on the poster as a graphic object, from a technological perspective, the aim is to highlight the opportunities and the constraints related to the technological evolution, with practical consequences on the designer’s work: from the analysis of the main strategies used in traditional and animated posters, one can conclude that graphic design principles are applied to both poster types, though the animated poster has a distinctive attracting tool which is animation. As the investigation is based on an intuitive methodology (based on bibliographical and iconographical sources and testimonies), the results may vary in the future, due to technological developments or others. The animated poster is still at its starting point, so the investigation does not trace the future, but tries to provide some evidence on its expected development: with the exponential increase on the number of screens in daily life, one can predict that the animated poster will gain more expression and relevance as an object of communication, triggering new transformations on the design process